Endocrine disruptors in the environment - Khetan, Sushil K. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
For most of the last decade, the science of endocrine disruption has evolved with more definitive evidence of its damaging potential to health and the environment. This book lists the major environmental chemicals of concern and their mechanism of endocrine disruption including remedial measures for them. Divided into three parts, it begins with an overview of the endocrine system and endocrine disruptors. It then goes on to cover hormone-signaling mechanisms, followed by various broad classes of putative endocrine disruptors, before introducing readers to environmental epigenetic modifications. Part two of the book focuses on removal processes of various EDCs by biotic and abiotic transformation/degradation. The last section consists of four chapters embracing themes on finding solutions to environmental EDCs. --
Environmental endocrine disruptors -- Mechanisms of endocrine system function -- Environmental chemicals targeting estrogen signaling pathways -- Anti-androgenic chemicals -- Thyroid-disrupting chemicals -- Activators of PPAR, RXR, AhR, and steroidogenic Factor 1 -- Effects of EDC mixtures -- Environmentally induced epigenetic modifications and transgenerational effects -- Biodegradations and biotransformations of selected examples of EDCs -- Abiotic degradations/transformations of EDCs Through oxidation processes -- Screening and testing programs for EDCs -- Trace contaminants: implications for water quality sustainability -- Policy and regulatory considerations for EDCs -- Green chemistry principles in the designing and screening for safe chemicals and remediation of EDCs.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Endocrine disrupting chemicals -- Environmental aspects; Endocrine disrupting chemicals -- Toxicity testing; Endocrine toxicology; Endocrine Disruptors -- toxicity; Endocrine Disruptors -- pharmacology; Environmental Pollutants -- toxicity; Environmental Pollution; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; Electronic books; Electronic books